Conditional privacy-preserving authentication with access likability for roaming service over internet of things - S Uma Priyadarsini, P; Sriramya, P (International Journal of Engineering and Technology, 2018)
Today the mobile subscribers can access the internet service whenever they want or wherever they are because of the roaming service. The necessity of accessing pervasively for the developing paradigm of networking such as the Internet of Things (IoT) is accomplished through this facility. In order to provide universal roaming service which is secure and privacy preserving at the multilevel, this paper proposes a privacy-preserving validation which is conditional with access likability called CPAL for roaming service. By utilizing a method of group signature it provides linking function of an anonymous user. This method has the capability to keep the identity of the users concealed and makes the authorized bodies possible to connect all the access information of the same user even without knowing the user’s real identity. In order to connect the access information from the user for enhancing the service, the foreign operators who are authorized or the service providers particularly uses the master linking key possessed by the trust linking server. In order to examine user’s likings, the individual access information is used but user’s identity is not disclosed. Subscribers can further make use of this functionality to probe the service usage without being identified. The proposed method also has the efficiency to simultaneously revoke a group of users. Comprehensive analysis of CPAL demonstrates that it can withstand many security threats and more adjustable in privacy preservation as compared to the other techniques. Assessment of its performance further proves the efficiency of CPAL with regards to communication and computation overhead. Future work would include the extension of CPAL scheme to effectively withstand internal attackers and design the lightweight secure and privacy-preserving scheme that will support IoT devices of large group.